The private and fiscal returns to higher education: A simulation approach for a young German cohort - Benjamin Fischer; Dominik Hügle (Freie Universität Berlin, School of Business & Economics, 2020)
We quantify the private and fiscal lifetime returns to higher education in Germany accounting for the redistribution through the tax-and-transfer system, cohort effects, and the effect of income pooling within households. For this purpose we build a dynamic microsimulation model that simulates individual life cycles of a young German cohort in terms of several key variables, such as employment, earnings, and household formation. To estimate the returns to higher education, we link our dynamic microsimulation model to a tax-benefit simulator that allows converting gross wages into disposable incomes. On average, we find private and fiscal returns that are substantially higher than current market interest rates. However, analyzing the distribution of returns we also find that there is a considerable share of young adults for whom we forecast vocational training, the alternative to higher education, to be financially more rewarding. We demonstrate how the taxtransfer system and income pooling within couple households affect private returns and decompose the fiscal returns into its major components.
urn:nbn:de:kobv:188-refubium-29097-0
Keywords: C53; I23; I26; 330; Higher education; Returns to education; Dynamic microsimulation